KETERSEDIAAN SUMBERDAYA LAHAN DAN AKSESBILITAS DALAM UPAYA MENDUKUNG PENYELENGGARAAN KETAHANAN PANGAN - Ari Tresna Sumantri; Nuniek Hermita; Rifqi Ahmad Riyanto; Asih Mulyaningsih (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This research entitled Land Resources and Accessibility to Support Food Security. This study aims to present information on the availability of land resources and accessibility in an effort to support food security in the Pandeglang Regency. The method used in this research is descriptive research model method with survey techniques. The results showed that the potential and availability of land in Pandeglang Regency is quite extensive, which is dominated by forestry, rice fields and large plantations with mixed forest data of 86,517.33 Ha or about 31% of the area of land use in Pandeglang Regency. Meanwhile, 18.24% of the area of land use in Pandeglang Regency with a land area of 50,888.90 hectares consists of shrubs. The area of rice fields 34,391.28 or about 12.32% of the area of land use and land use is 47,893.65 or 17% of the area of land use. Measurement of the aspect of access to food uses indicators related to the condition of the population, including the percentage of poor people with the number of poor people in Pandeglang Regency 115.90 (thousand people), the percentage of the population without access to electricity with data that almost 100 percent of households use electricity either from PLN or NonPLN, and the percentage of the population not working is around 41.56%. In addition, in the area of Pandeglang Regency there is a cooperative in the agricultural sector which is one of the infrastructure for providing food needs.